Coating material and coating film forming method
Patent Information
- Application Number
- JP2023194059
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-11-05
AI Technical Summary
Existing decorative finishing methods for buildings and civil engineering structures to achieve a natural stone-like finish with depth are complicated due to the need for separate processes to apply materials like mica.
A coating material comprising a resin component and specific aggregates in defined weight ratios, including scaly colored, granular translucent, and granular opaque aggregates, to create a natural stone-like finish with enhanced aesthetics.
The coating material easily imparts a sense of depth and improves aesthetic appearance by providing a natural stone-like finish.
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel coating material. [Background technology]
[0002] Conventionally, decorative finishing methods that impart the aesthetic appearance of natural stone to buildings and civil engineering structures have been known. In recent years, there have been an increasing number of cases where decorative finishing with designs that have the texture and depth unique to natural stone is desired. For example, Patent Document 1 describes such a method of forming a coating in which, after applying a main material, granular material made of mica and transparent and / or translucent aggregate is sprayed onto the surface of the main material before the main material dries. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 5-50025 Summary of the Invention [Problem to be solved by the invention]
[0004] However, as in Patent Document 1, in order to impart a natural sense of depth, it is necessary to apply a decorative material such as mica in a separate process, which may complicate the process. Under these circumstances, there is a demand for a coating material and a coating formation method that can easily achieve a natural stone-like finish with a sense of depth. [Means for solving the problem]
[0005] As a result of intensive research to solve the above problems, the inventors came up with the idea of easily achieving a finish with excellent aesthetics, such as a sense of depth, by using a coating material containing a resin component and a specific aggregate in a specific weight ratio, and thus completed the present invention. That is, the present invention has the following characteristics.
[0006] That is, the present invention has the following features. 1. A coating material comprising a resin component (A) and an aggregate (B), The coating material contains 100 to 2,000 parts by weight of aggregate (B) relative to 100 parts by weight of solid content of resin component (A), The aggregate (B) is a scale-like colored aggregate (b1), a granular translucent aggregate (b2), and a granular opaque Contains colored aggregate (b3), The weight ratio (b2) / (b1) of the scaly colored aggregate (b1) and the granular translucent aggregate (b2) is 5 / 1 to 180 / 1. the law of nature, The granular translucent aggregate (b2) contains 10 to 60% by weight of a granular translucent aggregate (b2') having an average particle size of 1 μm or more and less than 150 μm, The above-mentioned scaly colored aggregate (b1) is a scaly base particle that has been subjected to a coloring treatment, The granular translucent aggregate (b2) has a light transmittance of 3% or more and 50% or less, The granular opaque aggregate (b3) has a light transmittance of less than 3%. A coating material characterized by: 2. The coating material according to claim 1, characterized in that the weight ratio (b3) / (b1) of the scaly colored aggregate (b1) to the granular colored aggregate (b3) is 10 / 1 to 200 / 1. Or claim 2 2. A method for forming a coating film, comprising applying the coating material according to claim 1 to form a coating film. Effect of the Invention
[0007] According to the present invention, it is possible to impart design features such as a sense of depth and to improve the aesthetic appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described.
[0009] <Coating material> The coating material of the present invention is characterized by containing a resin component (A) and a specific aggregate (B) in a specific weight ratio.
[0010] Resin component (A) (hereinafter referred to as "component (A)") is not particularly limited, but is preferably at least one selected from water-soluble resins and water-dispersible resins. Examples of the resin include vinyl acetate resins, polyester resins, alkyd resins, vinyl chloride resins, epoxy resins, acrylic resins, urethane resins, acrylic silicone resins, fluororesins, and composites thereof. These resins can be used alone or in combination of two or more. These components (A) may also have crosslinking reactivity. When a component (A) having crosslinking reactivity is used, the water resistance, weather resistance, chemical resistance, and other properties of the coating can be improved.
[0011] The aggregate (B) (hereinafter referred to as "component (B)") contributes to excellent design. Such aggregate is not particularly limited as long as it is solid particle having some color effect, and either inorganic or organic material can be used, and either natural or artificial products can be used. Specific examples include ground materials such as heavy calcium carbonate, kansui stone, mica, kaolin, clay, china clay, china clay, talc, aluminum hydroxide, magnesium hydroxide, shells, barite powder, marble, granite, serpentine, granite, fluorite, feldspar, silica stone, and silica sand, ground ceramics, ground ceramics, glass beads, ground glass, inorganic particles such as metal pieces and metal powder, and organic particles such as resin beads, ground resins, rubbers, plastics, plant fibers, and plant pieces. Colored ones of these can also be used. By using one or more of these in combination, various natural stone-like colors can be expressed.
[0012] The (B) component is mixed in a ratio of 100 to 2000 parts by weight (preferably 150 to 1500 parts by weight, more preferably 200 to 1000 parts by weight) per 100 parts by weight of the solid content of the (A) component. By mixing the (B) component in such a ratio, a thick coating can be easily formed, the thickness of the formed coating can be enhanced, and a coating having water vapor permeability can be formed. In the present invention, "α to β" is synonymous with "α or more and β or less".
[0013] The present invention is characterized in that the component (B) contains a specific ratio of a scaly colored aggregate (b1), a granular translucent aggregate (b2), and a granular colored aggregate (b3), which imparts design features such as a sense of depth, a sense of luxury, and a sense of solidity, thereby improving the aesthetics.
[0014] The scaly colored aggregate (b1) (hereinafter referred to as "component (b1)") provides an accent design to the formed coating, enhancing its design. The size of component (b1) is preferably a long diameter of 0.5 mm or more (more preferably 1 mm or more), and a ratio of the short diameter to the long diameter (short diameter / long diameter) of 0.3 to 1. When the size of component (b1) satisfies the above range, its shape is easily recognized by the naked eye, making it suitable as an accent design. Note that the long diameter and short diameter of component (b1) are values measured by placing component (b1) stably and stationary on a horizontal surface and observing it from above using a microscope.
[0015] The thickness of the (b1) component is preferably 50 to 500 μm (more preferably 60 to 450 μm). In such a case, the (b1) component is easily transferred, and even if it is embedded in the coating, it can impart designability. In the present invention, the (b1) component preferably has a ratio of major axis to thickness that satisfies (major axis / thickness)>2 (more preferably 3, and even more preferably 5). The thickness of the (b1) component is a value measured with a micrometer.
[0016] Such a (b1) component may be, for example, a colored flake-like base particle. Specific examples of the base particle include inorganic pieces such as mica, sericite, clay, talc, plate-like kaolin, barium sulfate flakes, glass flakes, alumina flakes, shell pieces, and metal pieces, as well as rubber pieces, plastic pieces, and wood pieces. The coloring treatment is not particularly limited, but a method of coating the surface of the base particle with a colorant containing a pigment is preferred. The (b1) component may be used alone or in combination of two or more (one color or two or more colors), and various colors can be expressed.
[0017] The granular translucent aggregate (b2) (hereinafter referred to as "component (b2)") imparts transparency to the formed coating and enhances the design such as the sense of depth. In particular, in the present invention, the accent design of component (b1) can be seen through component (b2), which further enhances the sense of depth and is preferable in terms of improving aesthetics.
[0018] The (b2) component preferably has a light transmittance of 3% or more (more preferably 3% or more and 50% or less, and even more preferably 10% or more and 30% or less). In such a case, the above-mentioned effects can be sufficiently obtained. The light transmittance mentioned above is the total light transmittance measured by a turbidimeter. In this measurement, a sample of component (b2) is filled into a transparent glass cell having an inner thickness of 5 mm, and then water is gradually added. After that, air bubbles in the cell are removed by vibration.
[0019] Examples of such (b2) components include silica, calcium carbonate, sappanite, feldspar, quartz, etc., as well as crushed products thereof, crushed glass, glass beads, etc., and either colorless or colored types can be used as long as they satisfy the above-mentioned light transmittance. These can be used alone or in combination of two or more. Among these, in the present invention, it is particularly preferable to include one type selected from calcium carbonate and sappanite.
[0020] The average particle size of the (b2) component is preferably 1 μm or more and 1 mm or less (more preferably 2 μm or more and 800 μm or less, and even more preferably 3 μm or more and 600 μm or less). When this range is satisfied, the sense of depth of the formed coating can be enhanced.
[0021] The (b2) component is characterized in that the weight ratio (b2) / (b1) to the (b1) component is 5 / 1 to 180 / 1 (more preferably 8 / 1 to 150 / 1, and even more preferably 10 / 1 to 100 / 1). When this range is satisfied, the accent design of the (b1) component can be seen through the (b2) component, which gives a sense of depth and further enhances the aesthetic appearance.
[0022] Furthermore, in the present invention, it is preferable that the (b2) component contains a granular translucent aggregate (b2') having an average particle size of 1 μm or more and less than 150 μm (more preferably 2 μm or more and 100 μm or less, and even more preferably 3 μm or more and 80 μm or less). This makes the accent design of the formed coating more visible, and can enhance the sense of depth. The (b2') component is preferably 10 to 60% by weight (more preferably 15 to 55% by weight, even more preferably 20 to 50% by weight, and particularly preferably 25 to 45% by weight) in the (b2) component. In such a case, a portion where the (b2') is overlapped on the (b1) component is easily formed near the surface of the coating, and a sense of depth can be imparted to the accent design, so that the above effect can be further enhanced. The average particle size of component (b2) is an average value measured using a laser diffraction particle size distribution analyzer (measurement conditions: distribution standard: volume, refractive index: 1.60-0.10i).
[0023] The granular colored aggregate (b3) (hereinafter referred to as "component (b3)") is an opaque granular particle that mainly imparts color to the formed coating. As the component (b3), an opaque one with a light transmittance of less than 3% is preferable, and one with a light transmittance of 2% or less is more preferable. The light transmittance mentioned above is the total light transmittance measured by a turbidimeter. In this measurement, a sample of component (b3) is filled into a transparent glass cell having an inner thickness of 5 mm, and then water is gradually added. After that, air bubbles in the cell are removed by vibration.
[0024] The (b3) component may be any opaque material, such as marble, granite, serpentine, granite, fluorite, sapphire, feldspar, silica, quartz sand, and crushed products thereof, crushed porcelain, crushed ceramics, crushed glass, glass beads, crushed resin, resin beads, metal particles, etc., and those with colored coatings on the surface thereof, etc. By using one or more of these in combination, various natural stone-like colors can be expressed.
[0025] The average particle size of the (b3) component is preferably 5 μm or more and 1 mm or less (more preferably 8 μm or more and 800 μm or less, and even more preferably 10 μm or more and 600 μm or less). The average particle size of the (b3) component is a value obtained by sieving the particles using a metal mesh sieve specified in JIS Z8801-1:2000 and calculating the average weight distribution. Such a (b3) component is recognized as granular and is different from the scaly colored aggregate (b1).
[0026] In the present invention, it is preferable that the weight ratio (b3) / (b1) of the component (b3) to the component (b1) is 10 / 1 to 200 / 1 (more preferably 12 / 1 to 150 / 1, and even more preferably 15 / 1 to 100 / 1). When such a range is satisfied, the accent design is easily visible in the formed coating, and the aesthetic appearance can be further improved.
[0027] Furthermore, in the present invention, it is preferable that the weight ratio (b3) / (b2) of the (b3) component to the (b2) component is 0.1 / 1 to 15 / 1 (more preferably 0.2 / 1 to 10 / 1, and even more preferably 0.3 / 1 to 5 / 1). When this range is satisfied, the desired color can be imparted to the formed coating, and the hiding power of the entire coating can be ensured. Also, the visibility of the accent design can be improved.
[0028] In the present invention, the component (B) may contain, in addition to the components (b1), (b2), and (b3), for example, granular colored aggregate (b4) having an average particle size of more than 1 mm and not more than 10 mm, uncolored scale-like particles (b5), etc., so long as the effects of the present invention are not significantly impaired.
[0029] The coating material of the present invention can be produced by uniformly mixing the above-mentioned components by a known method, but if necessary, other components that can usually be used in coating materials can also be mixed in. Examples of such components include color pigments, extender pigments, fibers, film-forming assistants, thickeners, leveling agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, antifoaming agents, UV absorbers, light stabilizers, antioxidants, water, etc.
[0030] In the present invention, it is preferable to include an association type thickener as the thickener, and among them, a urethane association type thickener containing a hydrophobic group at the end and a urethane bond in the molecular chain is preferable. This can improve the transferability of the (b1) component, enhance the designability, and improve workability when forming a patterned coating by applying a coating material. The mixing ratio of the thickener is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, calculated as solid content, relative to 100 parts by weight of the solid content of the (A) component.
[0031] The viscosity of the coating material at the time of application (the viscosity after dilution, if diluted) is preferably adjusted to 20 to 200 Pa s (more preferably 50 to 150 Pa s), and the thixotropy index is preferably adjusted to 2.0 to 6.0 (more preferably 3.0 to 5.0). In the present invention, by setting the viscosity characteristics of the coating material under such conditions, the transferability of the above-mentioned component (b1) at the time of application is improved, which is advantageous in terms of improving coating workability and finish. In the present invention, the viscosity is a value determined by measuring the viscosity at 2 rpm (the indicator value at the second rotation) using a BH type viscometer. The thixotropy index (TI) is a value determined by the following formula using a BH type viscometer. The measurement temperature for both is 23°C. <Formula>TI=η1 / η2 (In the formula, η1 is the viscosity at 2 rpm (Pa s: indicator value at the second rotation). η2 is the viscosity at 20 rpm (Pa s: indicator value at the fourth rotation).)
[0032] <Film formation method> The coating material of the present invention is applied to a substrate to form a coating. The substrate constitutes the surface of a building, civil engineering structure, etc. Examples of such substrates include concrete, mortar, siding board, extrusion molding board, gypsum board, perlite board, plywood, brick, plastic board, metal plate, glass, porcelain tile, etc. These substrates may have a coating already formed on their surface, or may have wallpaper attached thereto, etc.
[0033] The coating material can be applied with a brush, trowel, roller, spray, etc. to form a coating. In particular, it is preferable to use a roller, trowel, etc., from the viewpoint of ease of application. In particular, the coating material of the present invention can form a coating having excellent water vapor permeability by forming an uneven coating with a roller.
[0034] The roller to be used is not particularly limited, but a porous roller can be suitably used in the present invention. A porous roller is a roller having a porous layer on the outer surface of a cylindrical core material, and the cylindrical core material is hollow so that a handle with a shaft can be attached, and the roller can be used by attaching a handle shaft to the hollow. The cylindrical core material is not particularly limited, and for example, a core material made of plastic, wood, paper, metal, etc. can be used. In order to increase the adhesion between the handle shaft and the core material, a reinforcing material made of, for example, plastic, rubber, glass, metal, fiber, etc. can be used between the handle shaft and the core material.
[0035] The porous roller used in the present invention is preferably one in which 50% or more of the pores on its surface (the outer surface of the porous layer) are 3 mm or more (preferably 50% or more of the pores are 3 mm or more and 8 mm or less, more preferably 60% or more of the pores are 3 mm or more and 8 mm or less, and even more preferably 70% or more of the pores are 3 mm or more and 8 mm or less). In the present invention, the size of the pores may be calculated by multiplying the maximum distance from the center of gravity of each pore by 2. The proportion of pores 3 mm or more in size is calculated by (the number of pores 3 mm or more appearing on the surface of the porous layer) / (the total number of pores appearing on the surface of the porous layer)×100(%).
[0036] Examples of such a porous layer include a porous layer having continuous pores, a porous layer having independent pores, etc., but in the present invention, a porous layer having continuous pores is preferred. The material thereof is not particularly limited, but examples thereof include acrylic resin, urethane resin, ester resin, ethylene resin, etc., and these resins that have been made porous in a sponge-like state are preferred.
[0037] The thickness of the porous layer is preferably 3 mm or more and 50 mm or less, more preferably 5 mm or more and 30 mm or less. With such a thickness, the coating material can be applied efficiently and the workability is excellent. The width (length) of the porous roller is not particularly limited, but is preferably about 80 mm or more and 250 mm or less, and the diameter (cylinder diameter) of the porous roller (including the porous layer) is preferably about 30 mm or more and 100 mm or less.
[0038] The amount of the coating material of the present invention to be applied is not particularly limited, but is preferably 0.5 to 6 kg / m 2 , more preferably 1 to 5 kg / m 2 When applied, the coating material of the present invention can be diluted with water. The dilution ratio is preferably 0 to 10% by weight. In such a case, the effect of the present invention can be fully exhibited.
[0039] The dry thickness of the coating material (formed coating) of the present invention is preferably 0.1 to 5 mm (more preferably 0.3 to 3 mm). When the formed coating has irregularities, the thickness of the concave and convex parts should be within the above range.
[0040] In addition, the coating film formed by the coating material of the present invention preferably has a water vapor permeability of 5 g / m2 at a dry thickness of 0.8 mm. 2 24 hours or more (preferably 10g / m 2 In the case of such a range, water vapor due to the moisture in the substrate can be sufficiently diffused, and swelling and peeling of the coating can be suppressed. The water vapor permeability in the present invention is measured in accordance with JIS K 5400-1990 8.17 "Water vapor permeability". EXAMPLES
[0041] The following examples will clarify the features of the present invention.
[0042] (Coating material 1~10) Based on the formulation shown in Table 1, each raw material was mixed by a standard method, and water was added so that the viscosity (BH type viscometer, 2 rpm) became 80 Pa s to produce coating materials 1 to 10. The TI values after dilution are also shown in Table 1.
[0043] The following components were used: (A) Acrylic silicone resin emulsion (solid content 50% by weight, medium: water) (B) Aggregate (b1) Scaly colored particles (black mica flakes, major axis: 1.4-3.8 mm, minor axis: 1.2-3.1 mm, thickness: 0.1-0.4 mm, minor axis / major axis (average): 0.92, major axis / thickness (average): 11.4) (b2) Granular translucent aggregate (kansuishite, average particle size: 200μm, light transmittance: 16%) (b2') Granular translucent aggregate (kansuishite, average particle size: 20μm, light transmittance: 16%) (b3-1) Granular colored aggregate (a mixture of white and beige silica sand, average particle size: 180 μm, light transmittance less than 1%) (b3-2) Granular colored aggregate (mixture of beige and brown silica sand, average particle size: 350 μm, light transmittance: 1% or less) ·Thickener 1 (urethane association type thickener) ·Thickener 2 (cellulose-based thickener) Additives (defoamers, etc.)
[0044] (Examples 1 to 7, Comparative Examples 1 to 3) On the base material (slate board) on which the undercoat was applied, the coating material was applied in an amount of 2 kg / m using a porous roller and coating material. 2 The paint was applied to the sample, and then dried and hardened at 23°C for 24 hours to form a patterned coating. The porous roller used had a diameter (cylinder diameter) of 70 mm, a roller width of 200 mm, a paper core, and a 15 mm thick porous layer made of urethane resin that had been made porous (with interconnected holes) like a sponge, with 82% of the surface of the porous layer being made up of pores measuring 3 mm to 8 mm.
[0045] <Evaluation> The following evaluations were carried out, and the results are shown in Table 4. Depth Sense Images with excellent depth perception were rated as "AA" and images with poor depth perception were rated as "D", and the ratings were made on a five-point scale: AA>A>B>C>D.
[0046] [Table 1]
[0047] In Examples 1 to 7, a beautiful natural stone-like coating having an accent design of black mica pieces was formed in a thin beige coating formed from the granular translucent aggregate and the granular colored aggregate. Furthermore, in Examples 1 to 3, there were areas on the surface of the black mica pieces where the granular translucent aggregate overlapped, and the black mica pieces could be seen through the granular translucent aggregate, forming a coating with an excellent sense of depth. In particular, in Example 1, the sense of depth of the black mica pieces was even more prominent. In addition, in Examples 4 and 5, the accent design by the black mica pieces was somewhat strong, while in Examples 6 and 7, the accent design by the black mica pieces was somewhat lacking, resulting in a coating that was somewhat inferior in the sense of depth compared to Examples 1 to 3. In Comparative Example 1, the accent design was insufficient, and a coating with poor depth was formed. In Comparative Example 2, the accent design by the black mica pieces was somewhat strong, and a coating with poor depth was formed. In Comparative Example 3, there was no accent design, and a coating with poor design was formed.
Claims
1. A coating material comprising a resin component (A) and an aggregate (B), The coating material contains 100 to 2,000 parts by weight of aggregate (B) per 100 parts by weight of solid content of resin component (A), The aggregate (B) includes a scaly colored aggregate (b1), a granular translucent aggregate (b2), and a granular opaque colored aggregate (b3), the weight ratio (b2) / (b1) of the scaly colored aggregate (b1) to the granular translucent aggregate (b2) is 5 / 1 to 180 / 1; The granular translucent aggregate (b2) contains 10 to 60% by weight of a granular translucent aggregate (b2') having an average particle size of 1 μm or more and less than 150 μm, The above-mentioned scaly colored aggregate (b1) is obtained by coloring scaly base particles, The granular translucent aggregate (b2) has a light transmittance of 3% or more and 50% or less, The coating material is characterized in that the granular opaque aggregate (b3) has a light transmittance of less than 3%.
2. 2. The coating material according to claim 1, wherein the weight ratio (b3) / (b1) of the scaly colored aggregate (b1) to the granular colored aggregate (b3) is 10 / 1 to 200 / 1.
3. A method for forming a coating film, comprising applying the coating material according to claim 1 or 2 onto a substrate to form a coating film.